Influence of ultrasonic cavitation on microstructure and mechanical response of an aluminum/alumina nanocomposite - Mohanty Pragyan (Science and Engineering of Composite Materials, 2016)
Nanocomposites of Al and Al2O3 were synthesized by an ultrasonic full cavitation technique which is a novel route for synthesis of uniformly distributed nanoparticles in metal matrix composites. The transmission electron micrograph indicates the uniform arrangement of nanoparticles throughout the metal matrix and the average size of the nanoparticles are in the order of 5 nm. The selected area electron diffraction analysis shows the presence of both Al and Al2O3 phases, which is also evidenced from the X-ray photoelectron spectroscopy analysis. The significant improvement in hardness and Young’s modulus due to the addition of a low weight fraction of nano-sized Al2O3 in aluminium infers that alumina nanoparticulates are distributed uniformly throughout the aluminium metal matrix. Hence, this paper shows a new method for inexpensive fabrication of bulk light weight metal matrix nanocomposites (MMNCs) by the use of noncontact full cavitation method.